2008
DOI: 10.1007/s00213-008-1315-4
|View full text |Cite
|
Sign up to set email alerts
|

Acute nicotine changes dynorphin and prodynorphin mRNA in the striatum

Abstract: We interpret our findings to indicate that acute nicotine enhances the synthesis and release of striatal Dyn. We propose that nicotine influences Dyn primarily through dopamine release and that glutamate plays a modulatory role. A heightened dynorphinergic tone may contribute to the aversive effects of nicotine in naive animals and first-time tobacco smokers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
40
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 47 publications
(45 citation statements)
references
References 74 publications
5
40
0
Order By: Relevance
“…This is followed by a return to baseline and a rebound elevation of DYN content lasting up to 24 h. Like other drugs of abuse, systemic nicotine administration elevates extracellular NAcc DA levels [156]. Not surprisingly, D1 and NMDA receptor blockade attenuate nicotine-induced DYN elevations [345], again, highlighting the role of D1-NMDA interactions in modulating DYN synthesis in response to various drugs of abuse. Nicotine produces biphasic motivational effects across doses.…”
Section: Nicotinementioning
confidence: 89%
See 2 more Smart Citations
“…This is followed by a return to baseline and a rebound elevation of DYN content lasting up to 24 h. Like other drugs of abuse, systemic nicotine administration elevates extracellular NAcc DA levels [156]. Not surprisingly, D1 and NMDA receptor blockade attenuate nicotine-induced DYN elevations [345], again, highlighting the role of D1-NMDA interactions in modulating DYN synthesis in response to various drugs of abuse. Nicotine produces biphasic motivational effects across doses.…”
Section: Nicotinementioning
confidence: 89%
“…Acute nicotine injection produces a dose-dependent increase in pdyn mRNA and DYN immunoreactivity in the striatum and NAcc [345]. PDYN elevations are long-lasting in striatum whereas peptide immunoreactivity is transiently increased (approx.…”
Section: Nicotinementioning
confidence: 96%
See 1 more Smart Citation
“…Concomitantly, NIC produces a significant decrease in native methionine-enkephalin (Met-Enk) levels in the central amygdala, flocculo-nodular lobe of the cerebellum, caudal part of the ventrolateral medulla, and the intermediolateral cell column of the spinal cord, reflecting release of the opioid peptide at these sites (11). Furthermore, Isola et al (12) reported that acute NIC (1 mg/kg, s.c.) induces an increase in striatal dynorphin 1-13 content and that prodynorphin mRNA levels were elevated in the striatum for a prolonged time (0.5 -24 h). The content of dynorphin 1-13 increased soon after the rise of prodynorphin mRNA, at 1 h after NIC.…”
Section: Nic and Endogenous Opioid Peptidesmentioning
confidence: 99%
“…While the majority of the CREB-regulated genes in the limbic system remain obscured, the precursor of the opioid peptide dynorphin (Dyn), prodynorphin (PD), has been identified as a CREB target . Acute nicotine elevates PD mRNA and enhances the synthesis and release of Dyn in caudate/putamen (CPu) and nucleus accumbens (NAc), an effect that has been associated with the aversive effects of the drug (Isola et al 2009). …”
Section: Introductionmentioning
confidence: 99%